Integrating Javanese Culture in Islamic Education: The Role of Pathok Negara Mosque - Salim, Ahmad Salim; Suyuti, Imam; Prihantoro, Wahyu Kholis; Muqorrobin, Ahmad; Nawangsasi, Esthi (Indonesian Journal of Islam and Muslim Societies, 2025)
This article examines Masjid Pathok Negara’s transformative role in preserving local wisdom in Yogyakarta, Indonesia. The Masjid Pathok Negara is the oldest mosque in Yogyakarta and possesses a distinctive history and architectural style. Additionally, this mosque serves as a hub for Islamic education, incorporating Javanese cultural principles into religious practices. This study employed a qualitative methodology with a case study approach, gathering data through observations, interviews, and documentation. The findings indicate that Masjid Pathok Negara plays a transformative role in upholding local traditions in Yogyakarta through various means, including (1) incorporating Javanese architectural elements, (2) applying the tridarma concept in mosque administration, (3) conducting Islamic education rooted in Javanese values, and (4) partnering with diverse stakeholders to harness the mosque’s potential. This article suggests that Masjid Pathok Negara may continue to uphold its identity as a mosque that honors Javanese culture and positively contributes to the surrounding community